PENGARUH MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE TERHADAP HASIL BELAJAR EKONOMI SISWA - Wakijo Wakijo; Lilian Mega Puri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2019)
Think Pair Share model is one of the cooperative learning method with syntax: think, pair, sharing answer and opinion that are able to change the assumption that the recitation method and the discussion that need to be organized in the setting of the whole group. This research aim to know the influence of using think pair share model for the student’s learning outcome of economic studies at SMA Negeri 1 Punggur that involved 126 students of 4 class at grade XI year 2018/2019. There are 32 students from XI IPS4 as sample and 31 students from XI IPS3 as control class. The instrument data collection retrieved by multiple choice test of 20 questions with 4 alternative options a-b-c-d. The questions is given to the students who have been given the experiment treatment and within treatment by the X variable. The results are proven by the analyze of thitung > ttabel , on the list of signification 5% i.e. 3.24 > 1.68 and at the significant level 1% i.e. 3.24 > 2.42. The conclusion of the hypothesis: there is positive influence by using cooperative learning think pair share model to increase the student’s learning outcome of economic studies at SMA Negeri 1 Punggur class XI IPS. Students who were declare pass with KKM=75 after being given the treatment as many as 26 and the students or as much as 81.25%, and the students who not pass as many as 6 peoples or 18.75%. Well then, the learning process can be said to be successful. Keyword: think pair share, learning outcome